Constituency in classifier expressions: Ch’ol and beyond - Dékány, Éva (Glossa (London), 2024)
This paper considers recent arguments from the literature that have been deemed supportive of the view that in Ch’ol (Mayan) numerals and classifiers form a constituent to the exclusion of the noun, and evaluates proposed diagnostics for prob- ing NP-internal constituency cross-linguistically. I show that the purported diagnostics are unsuitable as adjudicators of constituency both cross-linguistically and internally to Ch’ol. This is because the data involved in the tests are not uniquely compatible with [[Num Cl] N]; they can also be captured on [Num [Cl N]].